Laser cladding composite coating on mild steel using Ni–Cr–Ti–B4C powder. (1st December 2020) - Han, Tengfei; Xiao, Meng; Zhang, Jie; Feng, Xiaomei; Shen, Yifu
ABSTRACT: The composite coating was fabricated by laser cladding on Q235 mild steel. The cross-section morphology, microstructure, phase, micro-hardness and wear resistance of the coating were investigated by scanning electron microscope, energy dispersive spectrometry, X-ray diffraction, Vickers micro-hardness tester and dry sliding wear testing machine, respectively. Results showed that composite coating was gained without cracks and bonded with substrate excellently because of the prominent metallurgical bonding. The composite coating was made up of Ni3 Ti, Cr2 Ti, Ni–Cr–Fe, TiB2 and TiC. Ceramic reinforcements existed in coating with eutectic and independent structures. The micro-hardness of coating was about 5 times the substrate. Compared with substrate, the coating showed superior wear resistance.